Effects of collegial management leadership training programme on academic leaders’ transfer of training in a public university in Malaysia - Zulkifly, Nurul Afiqah (2021)
Nowadays leading a ‘republic of scholars’ in universities through hierarchical lens, is deemed an irrelevant approach. Collegial management leadership (CML) has been hugely lacking among academic leaders in Malaysian universities, although it can improve the performance of faculties. The Ministry of Higher Education (MOHE), Malaysia through its Higher Education Leadership Academy (AKEPT) emphasised the need for university academic leaders to be well-equipped with CML competencies. Therefore, this study aimed to measure the effects of collegial management leadership training (CMLT) programmes on transfer of training through participants’ perceived ability to practice the training conduct in their respective roles as leaders at a public university in Malaysia. This study integrated Baldwin and Ford’s (1988) transfer process model and Bess’ (1992) collegial model to measure the effects of the training interventions. Sixty university academic leaders comprising of deans, deputy deans, heads of departments and subject coordinators who are working in a public university in Malaysia participated in this study and they were non-randomly assigned to Cohort 1 (n=30) and Cohort 2 (n=30). This study adopted quasi-experimental design (pre-test and post-test, one group design) to determine the difference in training design (perceived content validity and transfer design), CML and transfer of training, before and after the training programmes. The two cohorts received structured CMLT programmes, namely CMLT-A (for Cohort 1) and CMLT-B (for Cohort 2). Both training programmes were guided by AKEPT’s CML module, but differs in training design, whereby CMLT-A incorporated one participant-centred learning tool (case study), while CMLT-B incorporated three. Participants were then assessed using a self-assessment survey questionnaire. Participants were assessed two times; before (pre-test) and after (post-test) the CMLT programmes, respectively. The post-test was administered six weeks after the training programme took place. The findings of this study suggested that most participants of Cohort 1 and Cohort 2 rated an increased level of training design, CML and transfer of training after they attended the training programme. There were positive, significant differences found between the pre- and post-test scores of training design, CML and transfer of training among both cohorts without controlling for covariates. However, after controlling for covariates, perceived content validity was found to be positive, significantly different among participants of Cohort 1. Nonetheless, only training participants of Cohort 2 showed positive, significant differences between the pre- and post-test scores of CML and transfer of training. In conclusion, CMLT-B programme affects transfer of training among the academic leaders. Behavioural level training evaluation is important to determine the effectiveness of a training programme. Furthermore, participantcentred learning tools, such as case study is crucial in designing an effective training programme. Through the amalgamation of transfer of training and collegial theories, this study theoretically confirmed and contributed to the HRD body of knowledge regarding the vitality of training design to best facilitate academic leaders’ transfer of training. Practically, this study may assist HRD units and the academic leaders to identify a working training design that allows participants to transfer the training through the use of participant-centred learning tools, such as case study.